‘To enlarge everything as a poet’: Drama and history in John Marston's The Wonder of Women, or, The Tragedie of Sophonisba - Zirak‐Schmidt, David Hasberg (Orbis litterarum, 2025)
This article advances two arguments about Marston's use and appropriation of history in The Wonder of Women, or, The Tragedie of Sophonisba. First, it argues that Marston transforms Sophonisba from a problematic femme fatale into a virtuous woman whose constancy in the face of adversity contrasts sharply with the political realities of the play. She is opposed both to the Machiavellianism of Carthage and Syphax's tyranny, and throughout the play she advocates political honesty, loyalty and patriotism. In extolling these virtues, Marston makes the Carthaginian heroine a moral exemplar for others to imitate and learn from. Second, Sophonisba is deeply concerned with theatre's role in making, remembering and interpreting history. This is expressed in Massinissa's adornment of Sophonisba's corpse at the end of the play, which leads to an on‐stage negotiation of her historical significance, and the heroine's acts of self‐historicisation. By this term I refer to a rhetorical strategy that Sophonisba uses throughout the play in order to reflect on the nature of history and her own place in it. Analysing this particular rhetorical strategy together with Marston's appropriation of the historical sources will allow for a reconsideration of Sophonisba as a historical and metahistorical play.